Quality of the Healthcare Services During COVID-19 Pandemic in Selected European Countries - Magdalena Tuczyńska; Rafał Staszewski; Maja Matthews-Kozanecka; Agnieszka Żok; Ewa Baum (Frontiers Media S.A., 2022)
BackgroundThere are several definitions of the quality of healthcare services. It may be defined as a level of value provided by any health care resource, as determined by some measurement. Scientists use a variety of quality measures to attempt to determine health care quality. They use special indicators or based on a patients' or healthcare professional's perception. This article aims to provide a short review of the available data on the quality of healthcare services in selected European countries during the COVID-19 pandemic.MethodologyThe research was done by the use of online databases such as PubMed, Google Scholar, and Science Direct. All the studies focused on the quality of healthcare services, yet the studies used different methods to measure this quality. In addition, the results of the authors' survey on the assessment of the quality of healthcare services before and during the COVID-19 pandemic were presented.ResultsAmong twelve studies, four were from the United Kingdom and one each of Catalonia, Italy, Sweden, Poland, Netherlands, France, Germany, Belgium. Patients in the United Kingdom felt that the quality of services was good during the pandemic, whereas the quality declined in the other studies cited. The results of our research also revealed a decrease in the quality of healthcare services provided.ConclusionsNevertheless the development of telemedicine has had a positive impact on the quality of healthcare services. The COVID-19 pandemic has undoubtedly affected most European countries' quality of healthcare services.